From Chamber-School to the «President Trujillo» School. Spatial and genealogical transformations in the Dominican rural school, 1844-1944 - Alfonseca Giner de los Rìos, Juan Bernardo (Historia y Memoria de la Educación, 2018)
The historical transition referred to in this paper describes the development of the modern mass schooling system in the Dominican Republic. It was partially public in its republican beginnings, when it emerged from the heart of the teacher’s home space under the model we call chamber-school, an education provided by the state that would slowly move towards more complete forms of free access to school. Between the 1844 quasi-public chamber-schools and the «Presidente Trujillo» schools of the 1930-1961 dictatorship, citizens’ open and free access to public education took place, accompanied by a profound transformation of spatial and social relations that gave life to the school. This paper analyzes the great transformation that the emergence of the «Presidente Trujillo» schools represented, as a school system based on a publicly- owned, isolated space, one which the rural population could access freely. Although we focus on the process of rural school spatial transformation, our main analytical interest lies in the configuration and change of social relationships that the development of public education entailed. We wish to understand both those relationships based on processes of power and interest derived from the articulation between the State and civil society; for example, those processes founded on the social epistemology that intended to regulate education during the first century of republican life of Dominican society (1844-1944).